Obscuring the speaker’s stance: when explicitating results in implicitation - Hirsch, Galia; Lessinger, Enora (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
The paradox that lies at the heart of the phenomenon of explicitation, taken as a broad category, is that explicitation on one level of analysis can correspond to implicitation on another. Some explicitations add or change linguistic elements to clarify the original text, others serve to reinforce the original speaker’s attitude; however, clarifying the text might in fact affect its global meaning, in particular when the text’s intention is precisely to remain obscure. In these cases, from a semantic or syntactic point of view, such translational shifts are explicitations, but on a deeper level of meaning, they can be considered implicitations, since they obscure the speaker’s stance, thus making the global meaning of the text more implicit. We thus advocate studying narratological explicitness from the angle of the more specific phenomenon of “reduction of complex narrative voices” (Chesterman 2010: 41).